PENGESAHAN IDENTITAS DALAM ASPEK HUKUM PADA PENETAPAN BEDA NAMA STUDI KASUS PERDATA NOMOR 43/PDT.P/2024/PN.TMG - Julisa Sistyawan, Dwanda; Fristianti, Nadya Dhea; Sarkanto, Sarkanto (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
The issue of legal identity plays a crucial role in legal and administrative processes, particularly when discrepancies arise in naming individuals, as seen in Case No. 43/Pdt.P/2024/PN Tmg involving Sabar and Sabar Widodo. This research adopts a normative juridical approach to analyze the legal principles surrounding establishing identity in official documents. Primary data were obtained from legal case files, while secondary data were gathered through literature reviews. The findings highlight that ambiguities in legal identity can lead to significant challenges, including inheritance rights disputes and administrative misrecognition. The case emphasizes the need for clear and accurate legal identities to ensure legal certainty and protect individual rights. The research underscores the importance of integrating digital signature technology and forensic linguistic expertise in verifying the authenticity of legal documents and identities. The court’s decision to declare that Sabar and Sabar Widodo refer to the same individual underscores the broader significance of identity clarity in legal contexts. This case reflects the need for legal reforms, including adopting modern digital tools to streamline the verification of identities and prevent potential disputes. The study highlights the necessity of a coherent legal framework to safeguard individual rights and ensure smooth administrative and legal procedures.